Perchlorate Environmental Occurrence, Interactions and Treatment - Gu, Baohua; Coates, John D. (Springer US : Imprint: Springer, 2006)
Perchlorate anion is a widespread, environmentally persistent contaminant recently discovered in U.S. groundwater and drinking water supplies that affect tens of millions of people. This book will summarize the most current knowledge and understandings of the extent of perchlorate contamination, chemical behavior, and recent development in innovative remediation technologies for perchlorate in the environment. Additionally, its natural occurrence and its unique isotopic signature (between natural and anthropogenic sources) and novel detection techniques are provided. The book is intended to provide the most comprehensive reference for environmental professionals, decision makers, geoscientists, university students and professors, and the general public. This book will provide a detailed description of the perchlorate chemistry and recent advances in innovative remediation technologies for perchlorate contamination and their pros and cons. Additionally, it will be the first book to describe the natural occurrence of perchlorate and its unique isotopic signatures for environmental forensics and its detection in the environment, particularly the real-time analysis using surface enhanced Raman spectroscopy.